Psychiatry in a War Situation: In Situ Therapeutic Approach to an Attack Case of Ber, Timbuktu in Mali - AZA-GNANDJI, Guy-Gérard (My University, 2023)
Objectives: At the beginning of 2012, northern Mali was occupied by several jihadist movements with the aim of creating a Khalifa that required the intervention of a UN peacekeeping mission after a war that slowed down their development. This mission is the deadliest in a complex attack and UN attack. This experience feedback in an international context of the resurgence of asymmetrical wars makes it possible to share in order to better anticipate and improve strategic approaches to assessments and therapeutic techniques. Description: After the presentation of the context with these particularities and the various adaptations, we made formulations of the missions such as lived and the details on the medico-psychological techniques used. The place of the brief physical examination should not be overlooked. The debriefings, even if they have proven themselves in the evaluation and prevention of psychotraumatic pathologies, must be adapted on a case-by-case basis in a certain programmed improvisation. Maintaining the site of the attack survivors without real military activities by reinforcing them with a new functional team was a decisive element in the mourning process according to their own statement. Conclusion: Forward psychiatry is a necessity in asymmetric warfare to maintain the operationality of the troops.
Keywords: Military Psychiatry; Blue Helmet; Attacks; Psychotrauma; UN Mission